EVALUASI TINGKAT KERUSAKAN JALAN DAN PENANGANAN PERBAIKAN RUAS JALAN DENGAN METODE BINA MARGA (Studi Kasus : Jalan Raya Halmahera Daerah Desa Jetis Kecamatan Blora Kabupaten Blora) - Rahmanto, Andi Rahmanto (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2024)
Jl.Raya Halmahera Daerah Desa Jetis Kecamatan Blora Kabupaten Blora is one of the national roads accesses between cities. leading to the many country.This road plays an important role in promoting economic growth, because this road is also access.The purpose of this study was to determine the type of damage and the level of road damage and provide alternative road damage repairs. A research site on the 1 km long , has one lanes and 4 m wide, type of flexural damage ( asphalt ), this study uses the methot of Bina Marga.There are 5 types of damage : Perforated ( 71,6963 m² ), Sink ( 88,794 m² ), Item Release ( 69,63193 m² ), Crack ( 68,901² ), Plot (102,4885 m² ). Total damage of 401,51 m² or 10,04 % of the total area of 4000 m². The most dominant damage is the type of damage item release 25,53%, patch 22,11% and disappear 17,86% of the total area of damage, causing inconvenience for motorists using the road, this occurs due to the development that occurs from other types of damage that are not immediately handled, the influence of weather ( especially rain ) which accelerates the formation of holes, and minor damage that occurs.Repair damage can be done by repairing according to the damage that occurred, appropriate improvement is ( patching ), and repainted ( overlay ) and further routine maintenance is carried out